Analysis of Monthly Temperature Changes Using Reanalysis Data in Yogyakarta for the Period 1970 - 2019 - Hasibuan, Muhammad Ansori; Aditya Prapanca; Rafif Firjatullah (Tinta Emas Institute, 2023)
Weather data is an essential record of various weather elements that serve as the basis for forecasting future weather and climate conditions. Managing large volumes of data requires appropriate methods and applications to process the data to produce accurate results. The data used is reanalysis data taken from Copernicus and its verifiers from observational data. Data processing using CDO tools. The results of this study show the RMSE value between the observation data and the model of 1.24, where the model data tends to be smaller than the observation data. Next, there was an increase in monthly average temperature during the period 1970 - 2019. A significant increase in temperature was seen from the period 1970 - 2019 the lowest average temperature was 26.09oC, 26.36oC, 26.45oC, 26.69oC and 26.96oC respectively. The monthly temperature increase reached 0.87oC during the period 1970 - 2019. This is clear evidence that climate change has occurred, characterized by significant temperature changes in the Yogyakarta region.